2021
DOI: 10.3390/children8080673
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxic Metal Mixtures and Preadolescent Kidney Function

Abstract: Exposure to metals including lead (Pb), cadmium (Cd), and arsenic (As), may impair kidney function as individual toxicants or in mixtures. However, no single medium is ideal to study multiple metals simultaneously. We hypothesized that multi-media biomarkers (MMBs), integrated indices combining information across biomarkers, are informative of adverse kidney function. Levels of Pb, Cd, and As were quantified in blood and urine in 4–6-year-old Mexican children (n = 300) in the PROGRESS longitudinal cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Estimated glomerular filtration rate, one of the classic markers of pediatric kidney function, has shown some moderately positive relationships with metal exposure, even when measured as a mixture. [ 85 ] Similar results in preclinical investigations demonstrated that metal mixtures (As, Cd, V, and Pb) in drinking water inhibited the initial phases of pronephros development in zebra fish embryos, which eventually resulted in poorly developed kidneys. Pronephros developmental frame is equivalent to about gestation period of 3–4 weeks in the human fetus.…”
Section: Multimetal Exposure‐associated Toxicity and Riskmentioning
confidence: 63%
“…Estimated glomerular filtration rate, one of the classic markers of pediatric kidney function, has shown some moderately positive relationships with metal exposure, even when measured as a mixture. [ 85 ] Similar results in preclinical investigations demonstrated that metal mixtures (As, Cd, V, and Pb) in drinking water inhibited the initial phases of pronephros development in zebra fish embryos, which eventually resulted in poorly developed kidneys. Pronephros developmental frame is equivalent to about gestation period of 3–4 weeks in the human fetus.…”
Section: Multimetal Exposure‐associated Toxicity and Riskmentioning
confidence: 63%
“…In Mexico, levels of Pb, Cd, and As were measured in urine and blood from adolescents from the PROGRESS longitudinal birth cohort study. This analysis found that the metal mixture in urine and blood are associated with increased eGFR and decreased cystatin C levels and that Cd and Pb are the main contributors of the mixture effects [53]. In addition, an analysis that included Cr and Li in the tooth-matrix from children from the same cohort found that exposure to a mixture of elements during the second and third trimester of gestation was the main window of vulnerability associated with children's decreased eGFR with Li and Cr as the main contributors of the mixture effect [54].…”
Section: Discussionmentioning
confidence: 94%
“…Long-term exposure to lead has been associated with cognitive decline and dementia among the elderly [90,91]. Lead also harms the vascular, renal, central and peripheral nervous systems [81,88,89,[92][93][94].…”
Section: Human Health Risk Assessmentmentioning
confidence: 99%